Intra-cultural Variation: Evidence and Implications for International Business - Au, Kevin Y. (Journal of International Business Studies, 1999)
This paper discusses the methodological and theoretical significance of intra-cultural variation (ICV)—the population distribution of a characteristic within a culture. A Monte Carlo study shows that ICV has substantial influence on the statistical power of cross-cultural tests. Therefore, studying ICV is methodologically important if we are to understand inconsistent findings and design cross-cultural studies with enough statistical power.